Design and energy integration of a lignocellulosic biorefinery - Νικλάνοβιτς, Δήμητρα (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Χημικών Μηχανικών. Τομέας Ανάλυσης, Σχεδιασμού και Ανάπτυξης Διεργασιών και Συστημάτων (ΙΙ), 2015)
In this thesis project a lignocellulosic biorefinery which produces a big number of useful biochemicals was designed and integrated. Part of this thesis project took place in collaboration with EPFL (École polytechnique fédérale de Lausanne), in Lausanne. The finite source of the fossil fuels, as well as their major contribution in the increase of GHG emissions, led the developed countries to seek out for alternative renewable energy sources. One of the most effective and abundant source of this kind, is the lignocellulosic feedstock. For this reason, wheat straw, which belongs to this category, was used as feedstock for the designed biorefinery. Its main components are cellulose, hemicellulose and lignin, to which wheat straw disintegrates through a complex organosolv pretreatment process. Each process included in the biorefinery was designed and simulated in Aspen Plus V7.2, by taking into consideration their properties and the bioconversion technologies through which they are produced. After the full completion of the process design of the biorefinery, thermal, mass and economic data were extracted from the simulation results and were used for the energy integration of the biorefinery The energy integration of each process in a biorefinery is extremely important in order to ensure big energy savings in the final plant. In this thesis project, the energy integration was estimated with two different approaches. Firstly, Osmose, a linear programming program, was used, which was developed in EPFL. This program provided the ability to calculate the size of the defined additional utilities for each chemical path of the biorefinery. Additionally, the possible profitability of each final product was calculated. The energy savings for the integrated chemical paths were also calculated. For the second approach, a program based on the transshipment model developed by Papoulias and Grossman was created in GAMS. This time, each process was integrated individually. However, the important difference is that during this process, the most cost-efficient utility combination, through a series of utility combinations, is pointed out. The Grand Composite Curves for each process were designed. Again, the energy savings for each integrated process were indicated. Through the comparison of the results of these two methods, useful conclusions can occur regarding the profitability the energy requirements of the final products.